Investigation of rhombohedral-cubic phase transition of La0.58Sr0.4Co0.2Fe0.8O3-δ using high temperature XRD. Issue 3 (15th February 2018) - Zou, Ying; Ziegner, Mirko; Malzbender, Jürgen; Krüger, Manja
Abstract: The phase transition of the La0.58 Sr0.4 Co0.2 Fe0.8 O3-δ oxygen transport membrane material has been investigated by X-ray diffraction at elevated temperatures. It has a rhombohedral symmetry at room temperature that transforms to a cubic symmetry at operation relevant higher temperatures, which was investigated in detail in the current work on the basis of bar type and powder specimens and discussed in terms of correlations with mechanical behavior.